Is it Permissible to Teach Buddhist Mindfulness Meditation in a Critical Thinking Course? - Vaidya, Anand Jayprakash (Informal Logic, 2020)
This essay argues for the permissibility of teaching Buddhist mindfulness meditation in a critical thinking course. One might object that Buddhist mindfulness meditation is part of a religion, and religions are thought to be dogmatic and uncritical, and thus inappropriate for a critical thinking course. However, I argue that there is a pathway from the importance of self-regulation for good critical thinking to the permissibility of including mindfulness meditation in a critical thinking course. I offer three arguments for the permissibility of inclusion: the self-regulation argument, the expansion by way of cognitive science argument, and the persistence through emotional volatil-ity argument. I then defend mindful-ness meditation as an appropriate form of meditation to include in a critical thinking course.